Theoretical and methodological foundations of psychological assistance to students with disabilities - Ananikova V. V. (The health of participants in the educational process: modern challenges and solutions, 2025)
The article discusses models of psychological assistance to students with disabilities. The basic principles of the organization of psychological examination and correction of developmental abnormalities are presented.
Keywords: инклюзивное образование; дефект; inclusive education; special educational needs; психологическая помощь; students with disabilities; defect; psychological assistance; areas and models of psychological assistance; developmental abnormalities (dysontogenies); mental dysontogenesis; normotypic students; направления и модели психологической помощи; обучающиеся с ограниченными возможностями здоровья (ОВЗ); особые образовательные потребности (ООП); отклонения (аномалии) в развитии (дизонтогении); психический дизонтогенез; нормотипичные обучающиеся